A revision of the endemic South African sac spider genus Lessertina Lawrence, 1942 (Araneae: Eutichuridae) - Haddad, Charles R. (Zootaxa, 2014)
The endemic South African sac spider genus Lessertina Lawrence, 1942, previously known only from the type species (L. mutica Lawrence, 1942), is revised. Both sexes of L. mutica are redescribed and the species is recorded from the Eastern Cape, KwaZulu-Natal and Limpopo Provinces. A new species, L. capensis sp. nov., is described from the Eastern and Western Cape Provinces.